2013
DOI: 10.5935/2177-4560.20130001
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of water quality of Rio Bonzinho in the city of Ji-Paraná, RO

Abstract: ResumoO objetivo do trabalho foi avaliar a qualidade das águas do igarapé Bonzinho da cidade de Ji-Paraná -RO. Após estabelecidos 02 pontos de amostragemno igarapé. Foram analisadas as seguintes variáveis de qualidade: coliformes fecais, demanda bioquímica de oxigênio -DBO, fosfatos, nitratos, oxigênio dissolvido -OD, pH, sólidos totais, temperatura e turbidez. Os resultados foram analisados frente aos padrões de qualidade para Classe 2 e agrupados para o cálculo do Índice de Qualidade da Água (IQA). A maioria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
1
0
0
Order By: Relevance
“…Similar results were reported by Vieira et al (2013) at the collection sites of the River Bonzinho in the state of Roraima, Brazil. These authors reported fecal coliforms rates between 400 and 700 NMP 100 mL -1 , which failed to comply with those given by the Brazilian Health Ministry, or rather, more than 100 mL of fecal contamination.…”
Section: Social and Environmental Assessmentsupporting
confidence: 77%
“…Similar results were reported by Vieira et al (2013) at the collection sites of the River Bonzinho in the state of Roraima, Brazil. These authors reported fecal coliforms rates between 400 and 700 NMP 100 mL -1 , which failed to comply with those given by the Brazilian Health Ministry, or rather, more than 100 mL of fecal contamination.…”
Section: Social and Environmental Assessmentsupporting
confidence: 77%